PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN TENTANG PERSONAL HYGIENE SAAT MENSTRUASI DALAM PENCEGAHAN PRURITUS VULVAE PADA REMAJA PUTRI DI SMK PAB 8 SAMPALI - Lubis, Anita Damayanti; Zaen, Niasty Lasmy (Universitas Murni Teguh, 2025)
Adolescents who do not know the importance of personal hygiene during menstruation will face problems in their reproductive organs which often occur is pruritus vulvae so that health education is needed in adolescents in improving health services in adolescents. The purpose of this study was to determine the effect of health education on knowledge about personal hygiene during menstruation in the prevention of pruritus vulvae in adolescent girls at SMK PAB 8 Sampali in 2024. This study used a quantitative method with a One Group Pretest-Posttest Pre-Experiment design. The population consisted of all X and XI grade students, with a total of 167 people. A sample of 53 students was taken using probability sampling technique, namely proportionate stratified random sampling. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed that before health education, the majority of schoolgirls had poor knowledge (22 students or 41.5%). After health education, the majority of schoolgirls' knowledge became good (49 schoolgirls or 92.5%). The conclusion of this study is that there is a significant effect of health education on increasing the knowledge of female students about personal hygiene during menstruation in preventing pruritus vulvae. Schools are advised to facilitate female students with reliable health information through books, journals, or cooperation with the nearest health care facility. Abstrak Remaja yang kurang mengetahui pentingnya personal hygiene pada saat menstruasi akan menghadapi masalah pada organ reproduksinya yang sering terjadi adalah pruritus vulvae sehingga pendidikan kesehatan sangat diperlukan pada remaja dalam meningkatkan pelayanan kesehatan pada remaja. Tujuan penelitian ini untuk mengetahui pengaruh pendidikan kesehatan terhadap pengetahuan tentang personal hygiene saat menstruasi dalam pencegahan pruritus vulvae pada remaja putri di SMK PAB 8 Sampali Tahun 2024.Penelitian ini menggunakan metode kuantitatif dengan desain Pre-Eksperimen One Group Pretest-Posttest. Populasi terdiri dari seluruh siswi kelas X dan XI, dengan total 167 orang. Sampel sebanyak 53 siswi diambil menggunakan teknik probability sampling, yaitu proportionate stratified random sampling. Data dianalisis menggunakan uji Wilcoxon Signed Rank Test. Hasil penelitian menunjukkan bahwa sebelum pendidikan kesehatan, mayoritas siswi memiliki pengetahuan kurang (22 siswi atau 41,5%). Setelah pendidikan kesehatan, pengetahuan siswi mayoritas menjadi baik (49 siswi atau 92,5%). Kesimpulan penelitian ini adalah adanya pengaruh signifikan pendidikan kesehatan terhadap peningkatan pengetahuan siswi tentang personal hygiene saat menstruasi dalam pencegahan pruritus vulvae. Sekolah disarankan memfasilitasi siswi dengan informasi kesehatan yang terpercaya melalui buku, jurnal, atau kerjasama dengan fasilitas pelayanan kesehatan terdekat.